2014
DOI: 10.1080/14675986.2014.883167
|View full text |Cite
|
Sign up to set email alerts
|

A multilingual approach to analysing standardized test results: immigrant primary school children and the role of languages spoken in a bi-/multilingual community

Abstract: The present study adopts a multilingual approach to analysing the standardized test results of primary school immigrant children living in the bi-/multilingual context of South Tyrol, Italy. The standardized test results are from the Invalsi test administered across Italy in 2009/2010. In South Tyrol, several languages are spoken on a daily basis and the long-established ethnic groups are speakers of German (69%), Italian (26%) and Ladin (4%). While the language of instruction for immigrant children attending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In the current educational zeitgeist, norm-referenced standardized assessment methods are increasingly being used to assess where a given student is academically located, compared to their peers. These forms of assessment are usually administered in the country's official language(s) of instruction (De Angelis, 2014) and make use of a Eurocentric approach to learning (Ryan et al, 2013). However, many studies have demonstrated the need for more culturally appropriate assessment methods specifically with regard to newly immigrated EAL students and FNMI students (De Angelis, 2014;Sefa Dei & McDermott, 2014;James, 2017;Ryan et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current educational zeitgeist, norm-referenced standardized assessment methods are increasingly being used to assess where a given student is academically located, compared to their peers. These forms of assessment are usually administered in the country's official language(s) of instruction (De Angelis, 2014) and make use of a Eurocentric approach to learning (Ryan et al, 2013). However, many studies have demonstrated the need for more culturally appropriate assessment methods specifically with regard to newly immigrated EAL students and FNMI students (De Angelis, 2014;Sefa Dei & McDermott, 2014;James, 2017;Ryan et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These forms of assessment are usually administered in the country's official language(s) of instruction (De Angelis, 2014) and make use of a Eurocentric approach to learning (Ryan et al, 2013). However, many studies have demonstrated the need for more culturally appropriate assessment methods specifically with regard to newly immigrated EAL students and FNMI students (De Angelis, 2014;Sefa Dei & McDermott, 2014;James, 2017;Ryan et al, 2013). In fact, monolingual biases resulting from the administration of standardized assessments (Brown, 2013) have been shown to be an unfair practice regarding multilingual students as they are asked to perform in a second language and thus have lower chances of succeeding, compared to their monolingual peers (May, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In practice, the standardized aptitude examination is far from fair. Even though some researchers (Berry et al, 2014; Duran, 1983; Engelhard et al, 2014; Pennock-Roman, 1990; Scheiber, 2017; Zwick & Sklar, 2005), for example, state that bilingual students do relatively poorly on standardized aptitude and entrance examinations simply because this is a reflection of their poor academic achievement in the educational settings overall, an overwhelming amount of research does show that those students for whom English is not a first language or those students who are bilingual, do not score as well in the aptitude test as their first language English-speaking peers and their monolingual English-speaking peers (Angelis, 2014; Haitana et al, 2010; Saenz & Huer, 2003; White & Jin, 2011). Pearson (1993) has studied bilingual students, comparing them with monolingual students in Florida with regard to their SAT scores and their grade point average (GPA) scores to see whether bilingual students perform at a relatively lower level than their monolingual peers or if they perform on par with their monolingual peers.…”
Section: The Bilingual and The Minority Studentmentioning
confidence: 99%